Strong Margin Influence on the Arctic Ocean Barium Cycle Revealed by Pan‐Arctic Synthesis. Issue 4 (30th March 2022) - Whitmore, Laura M.; Shiller, Alan M.; Horner, Tristan J.; Xiang, Yang; Auro, Maureen E.; Bauch, Dorothea; Dehairs, Frank; Lam, Phoebe J.; Li, Jingxuan; Maldonado, Maria T.; Mears, Chantal; Newton, Robert; et al.
Abstract: Early studies revealed relationships between barium (Ba), particulate organic carbon and silicate, suggesting applications for Ba as a paleoproductivity tracer and as a tracer of modern ocean circulation. But, what controls the distribution of barium (Ba) in the oceans? Here, we investigated the Arctic Ocean Ba cycle through a one‐of‐a‐kind data set containing dissolved (dBa), particulate (pBa), and stable isotope Ba ratio (δ 138 Ba) data from four Arctic GEOTRACES expeditions conducted in 2015. We hypothesized that margins would be a substantial source of Ba to the Arctic Ocean water column. The dBa, pBa, and δ 138 Ba distributions all suggest significant modification of inflowing Pacific seawater over the shelves, and the dBa mass balance implies that ∼50% of the dBa inventory (upper 500 m of the Arctic water column) was supplied by nonconservative inputs. Calculated areal dBa fluxes are up to 10 μmol m −2  day −1 on the margin, which is comparable to fluxes described in other regions. Applying this approach to dBa data from the 1994 Arctic Ocean Survey yields similar results. The Canadian Arctic Archipelago did not appear to have a similar margin source; rather, the dBa distribution in this section is consistent with mixing of Arctic Ocean‐derived waters and Baffin Bay‐derived waters. Although we lack enough information to identify the specifics of the shelf sediment Ba source, we suspect that a sedimentary remineralization and terrigenous sources (e.g., submarine groundwater discharge or fluvial particles) are contributors. Plain Language Summary: We investigated the barium (Ba) cycle in the Arctic Ocean. The oceanic Ba cycle is supported by the interplay of seawater mixing, river inputs, sediment inputs, and particle formation and export from the water column. We determined that the distribution of dissolved Ba in the upper 500 m of the Arctic Ocean is largely set by a shelf sediment source; this is newly described, as previous literature assumed rivers and seawater mixing were the predominant contributors to the distribution. This discovery fits in with recent findings that the shelf sediments are a major source of radium and other trace metals to the surface Arctic Ocean. This is important to consider as the warming climate continues to erode Arctic ice cover (sea ice or glacial). Monitoring the relative sources of Ba to the water column can help define how warming impacts Arctic Ocean biogeochemistry. Key Points: A mass balance approach indicates margin sources of barium (Ba) account for ∼50% of the budget Amerasian Arctic Ocean samples exhibit inverted Ba isotope profiles, though still fall on the global array Particle supply from the shelves and dissolution in the deep Amerasian Arctic Ocean is a likely source of dissolved Ba